ANALISIS KUALITAS MINYAK GORENG BERDASARKAN SUHU PEMANASAN DENGAN METODE KOEFISIEN VISKOSITAS FALLING BALL - Khaeratin Shoaliha; Kurniawan Arizona; Bahtiar Bahtiar (Universitas Mataram, 2020)
This study aims to determine the effect of temperature on oil viscosity or viscosity using the falling ball method. The approach in this study uses a quantitative approach to the type of laboratory experimental research. The population of this research is cooking oil, by taking three types of oil samples. The three types consisted of palm oil, coconut, and olive which were then observed for their effects on temperature using the fall ball method. Data were collected through laboratory experiments with measurements three times using the falling ball viscosity method. The data analysis technique used is regression analysis. Based on tests that have been done, it can be observed that palm oil before it is heated has a viscosity value of 0.885 Ns / m2, when palm oil is heated to temperatures of 40˚C, 60˚C, 80˚C, and 100˚C the viscosity value changes to 0.854 Ns / m2, 0.754 Ns / m2, 0.828 Ns / m2 and 0.616 Ns / m2. Coconut oil before heating has a viscosity value of 0.828 Ns / m2, when heated with the same temperature the viscosity value changes to 0.666 Ns / m2, 0.588 Ns / m2, 0.572 Ns / m2, and 0.524 Ns / m2. Olive oil before heating has a value of 0.919 Ns / m2, when it is heated the value decreases to 0.869 Ns / m2, 0.774 Ns / m2, 0.746 Ns / m2, and 0.680 Ns / m2. Correlation value obtained based on data calculations is -0.616 meaning that temperature and viscosity have a strong relationship, a negative sign indicates that the relationship is inversely proportional. It can be seen that there is an effect of viscosity value on cooking oil temperature.